The lies we leave behind [large type] - Salazar, Noelle (Thorndike Press large print historical fiction., 2025)
Somewhere in the Pacific, 1943. Kate Campbell is a nurse who bravely flies back and forth from the front to rescue wounded soldiers, amid long days, harsh conditions and often dangerous weather. Driven by a deep personal need to help in the war effort, she is conflicted when an injury results in her reassignment to the relative comfort of the English countryside.Love has never been part of her plan, but despite herself, she falls for an officer with three bullet wounds, startling blue eyes and a wicked sense of humor. For the first time, Kate sees a future far from the horrors of war and hate. But before she can pursue it, a secret from her past calls her to duty, and she'll have to travel back into danger one more time to rescue a part of herself she'd left behind. But will she make it back? And will that future still be waiting for her if she does?